2018
DOI: 10.3847/1538-4365/aad95f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jupiter's Formation on the Distribution of Refractory Elements and Inclusions in Meteorites

Abstract: We present a comprehensive evolutionary model of the Sun's protoplanetary disk, constructed to resolve the "CAI Storage" problem of meteoritics. We predict the abundances of calcium-rich, aluminum-rich inclusions (CAIs) and refractory lithophile elements under the central assumption that Jupiter's ∼ 30 M ⊕ core forms at about 3 AU at around 0.6 Myr and opened a gap CAIs are trapped in the pressure maximum beyond Jupiter; carbonaceous chondrites formed there. Inside Jupiter's orbit, CAIs were depleted by aerody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
257
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(279 citation statements)
references
References 257 publications
(336 reference statements)
19
257
3
Order By: Relevance
“…This is supported by the models of Desch et al. (), which suggest that the outward movement of Jupiter began shortly before the CB chondrites were produced by a catastrophic impact. If the igneous fragment was formed within the or close to the formation region of CB chondrites, it was also formed beyond Jupiter in the carbonaceous chondrite region.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This is supported by the models of Desch et al. (), which suggest that the outward movement of Jupiter began shortly before the CB chondrites were produced by a catastrophic impact. If the igneous fragment was formed within the or close to the formation region of CB chondrites, it was also formed beyond Jupiter in the carbonaceous chondrite region.…”
Section: Discussionsupporting
confidence: 56%
“…Based on Mo-isotopes, Budde et al (2016) showed that CB chondrites belong to the group of carbonaceous chondrites and were most likely formed beyond Jupiter together with CM, CO, CK, CV, CB, and CR chondrites. This is supported by the models of Desch et al (2018), which suggest that the outward movement of Jupiter began shortly before the CB chondrites were produced by a catastrophic impact. If the igneous fragment was formed within the or close to the formation region of CB chondrites, it was also formed beyond Jupiter in the carbonaceous chondrite region.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A popular add-on in recent literature is to consider that the aforementioned Jupiter-carved gap pressure maximum filtered out dust drifting inward past it (e.g. Desch et al 2018;Nanne et al 2019), sealing off the inner disk from the outer disk. It is uncertain, though, whether the dust flow would be significantly interrupted given the size sensitivity of this concentration process (Haugbølle et al 2019).…”
Section: The Carbonaceous/non-carbonaceous Chondrite Dichotomymentioning
confidence: 99%
“…Since the space-time ordering of the different chondrite groups, or even the above broad superclans, is anything but understood (e.g . Wood 2005;Chambers 2006;Jacquet 2014b;Desch et al 2018), these isotopic systematics represent critical constraints to rationalize.…”
Section: Introductionmentioning
confidence: 99%